THE BIOGEOCHEMICAL CONSEQUENCES OF THE MID-CRETACEOUS SUPERPLUME - Hope Jahren A. (My University, 2002)
Superplumes have been put forward as a driving mechanism for a variety of global phenomena, ranging from geomagnetic reversal anomalies to global climate warming via massive additions of volcanic CO2. Here I propose that rates of uplift caused by modern superplumes would result in the liberation of hundreds of Gt of carbon from methane clathrates on a timescale from tens to hundreds of millions of years. The associated eruption of the Ontong-Java flood basalts would additionally destabilize hundreds of Gt of carbon from methane hydrates during the Aptian-Albian. Evidence of this methane release is recorded in the early Aptian (ca. 117 Ma) carbon isotope records of marine carbonate, marine organic carbon, and terrestrially photosynthesized carbon as a 3-5%% negative excursion. As this methane release was oxidized within the biosphere, it would have resulted in massive chemical cycling disruption within the ocean and on land, including widespread oceanic anoxia, and the out-competition of conifers by angiosperms at mid- and high-latitudes.
Keywords: Cretaceous; Albian; Aptian; Mesozoic::Cretaceous; Mesozoic::Cretaceous::Lower::Albian; Мезозой::Меловая::Нижний::Альбский; Мезозой::Меловая::Нижний::Аптский; Мезозой::Меловая; Mesozoic::Cretaceous::Lower::Aptian